(untitled) (Archives of Mechanics - Test, 2000)
In numerical analyses of fatigue damage evolution in metal matrix composites, the development of final failure and the subsequent crack growth in the material are accounted for. Cell model analyses are used for aluminium reinforced by short SiC fibres, with the matrix material represented by a cyclic plasticity model, in which continuum damage mechanics is incorporated to model fatigue damage. The Bauschinger effect, ratchetting, mean stress relaxation, and cyclic hardening or softening can be accounted for by the material model, as is important in studies of low cycle fatigue. Different fibre aspect ratios and spacings are studied for different loading cases.